INFLUENCE OF PARENTING STYLES ON THE ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN NIGER STATE - Femi, Ogunsola (International Journal of Research -GRANTHAALAYAH, 2018)
The study examined the effects of parenting styles on the academic performance of secondary school students in Niger state, using the Ex – Post Facto design. Two hypotheses were formulated. Sample for the study were 600 SS 2 students randomly selected from 30 secondary schools within the state, using a researcher developed Parenting Style Questionnaire (PSQ) and Standardised Students Continuous Assessment Scores (SCAS) in English and Mathematics. Data was analysed using a One – Way Analysis of Variance (ANOVA). Results showed that neither parenting styles nor parenting styles of supervision of children`s schoolwork have significant effect on students’ academic performance. These findings are an indication of the apparent less commitment of parents in their parenting roles. It was recommended that guidance and counselling seminars should be organised for parents on effective parenting skills